Syntheses of Bi2X3 (X = S, Se, Te) from elements under hydrothermal conditions - Keitaro Tezuka; Saori Kase; Yue Jin Shan (Journal of Asian Ceramic Societies, 2014)
Bismuth chalcogenides (Bi2X3, X = S, Se, Te) were synthesized from the elements under hydrothermal condition. Single phases of Bi2S3 and Bi2Se3 were produced at 240 °C. Bi2Te3 was obtained as an almost single phase with a small amount of Bi2TeO5. From the results of control experiments without water, the hydrothermal condition in the production of Bi2S3 was more effective than that of Bi2Se3. The particles of obtained Bi2S3 were spherical, with a diameter of ∼1 μm. The Bi2Se3 particles were in a plate-like form, with a width of ∼1 μm and a thickness of ∼0.2 μm.